Understanding Inclusive School Culture Through the Index for Inclusion: Empirical Findings from Primary Schools in Asahan Regency, Indonesia - Nicki Andrina Sari; Damri, Damri; Mega Iswari; Antoni Tsaputra; Rahmahtrisilvia, Rahmahtrisilvia; Amani, Risca (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to examine the culture dimension of the Index for Inclusion in public primary schools implementing inclusive education in Asahan Regency, Indonesia. Employing a quantitative descriptive survey approach, the investigation involved 35 teachers selected through purposive sampling from seven designated inclusive public primary schools (UPTD SDN) based on their direct instructional experience in inclusive classrooms. Data were collected using an adapted questionnaire measuring Dimension A (Creating Inclusive Cultures) of the Index for Inclusion and analyzed through descriptive statistics. The findings revealed that the participating schools demonstrated a relatively strong inclusive culture, with descriptive statistical analyses revealed that the participating schools demonstrated a high level of inclusive culture, with an overall composite mean score of 1.91 (SD = 0.28) on a three-point scale (ranging from 0.00 to 2.00). Across subdimensions, Building Community achieved a higher mean score (M = 1.93, SD = 0.24), led by peer assistance (M = 1.97, SD = 0.17), whereas Establishing Inclusive Values scored slightly lower (M = 1.88, SD = 0.33), with institutional anti-discrimination practices recording the lowest mean (M = 1.85, SD = 0.36). These empirical findings indicate that principles of participation, equity, and respect for diversity are well-integrated into the school culture, while underscoring the necessity of reinforcing family engagement and explicit anti-discrimination initiatives within primary schools.